A sum

Calculus Level 2

n = 1 2 2 n 1 2 2 n + 1 = a b \large \sum_{n=1}^{\infty} \frac{2^{2^{n}}-1}{2^{2^{n+1}}} = \frac ab

If the equation above holds true for coprime positive integers a a and b b , find the value of a + b a+b .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Chew-Seong Cheong
Jan 31, 2017

S = n = 1 2 2 n 1 2 2 n + 1 = 2 2 1 2 4 + 2 4 1 2 8 + 2 8 1 2 16 + 2 16 1 2 32 + . . . = 1 2 2 1 2 4 + 1 2 4 1 2 8 + 1 2 8 1 2 16 + 1 2 16 1 2 32 + . . . = 1 2 2 = 1 4 \begin{aligned} S & = \sum_{n=1}^\infty \frac {2^{2^n}-1}{2^{2^{n+1}}} \\ & = \frac {2^2-1}{2^4} + \frac {2^4-1}{2^8} + \frac {2^8-1}{2^{16}} + \frac {2^{16}-1}{2^{32}} + ... \\ & = \frac 1{2^2} - \frac 1{2^4} + \frac 1{2^4} - \frac 1{2^8} + \frac 1{2^8} - \frac 1{2^{16}} + \frac 1{2^{16}} - \frac 1{2^{32}} + ... \\ & = \frac 1{2^2} \\ & = \frac 14 \end{aligned}

a + b = 1 + 4 = 5 \implies a+b = 1+4 = \boxed{5}

Moderator note:

In dealing with sum-notation, it can be extremely helpful to simply expand into individual terms; here the pattern which allows terms to cancel then becomes much more visible.

LaTeX: S = n = 1 2 2 n 1 2 2 n + 1 = n = 1 [ 2 2 n 2 2 n + 1 1 2 2 n + 1 ] S_{\infty} = \displaystyle\sum_{n=1}^{ \infty} \frac{2^{2^n} - 1}{2^{2^{n+1}}} = \displaystyle\sum_{n=1}^{ \infty} [\frac{2^{2^n}}{2^{2^{n+1}}} - \frac{1}{2^{2^{n+1}}}]

LaTeX: n = 1 [ 2 2 n 2 2 n × 2 2 1 2 2 n × 2 2 ] = n = 1 [ 1 2 2 1 2 2 n × 2 2 ] = 1 4 × n = 1 [ 1 1 2 2 n ] \displaystyle\sum_{n=1}^{ \infty} [\frac{2^{2^n}}{{2^{2^n}} \times {2^2}} - \frac{1}{{2^{2^n}} \times {2^2}}] = \displaystyle\sum_{n=1}^{ \infty} [\frac{1}{2^2} - \frac{1}{{2^{2^n}} \times {2^2}}] = \frac{1}{4} \times \displaystyle\sum_{n=1}^{ \infty}[1 - \frac{1}{2^{2^n}}]

LaTeX: lim n 1 2 2 n = 0 + \lim_{n \to \infty} \color{#3D99F6}{\frac{1}{2^{2^n}}}= 0^+ and LaTeX: lim n 1 1 2 2 n = 1 + 0 + = 1 \lim_{n \to \infty} \color{#3D99F6}{1 - \frac{1}{2^{2^n}}} = 1 +0^+ = 1

Then LaTeX: lim n S = 1 4 × 1 = 1 4 \lim_{n \to \infty} S_{\infty} = \frac{1}{4} \times 1 = \color{#3D99F6}{\boxed{\frac{1}{4}}}

Then we have : LaTeX: a + b = 1 + 4 = 5 a + b = \color{#D61F06}{\boxed{ 1 + 4 = 5}}

Frédéric Deleria - 4 years, 1 month ago

Log in to reply

There's an error in the calculations here. 2 2 n + 1 = 2 2 n × 2 2 n 2^{2^{n+1}} = 2^{2^{n}} \times 2^{2^{n}} . So 2 2 n 1 2 2 n + 1 = 2 2 n 2 2 n × 2 2 n 1 2 2 n × 2 2 n = 1 2 2 n × ( 1 1 2 2 n ) \frac{2^{2^{n}}-1}{2^{2^{n+1}}}=\frac{2^{2^{n}}}{2^{2^{n}}\times2^{2^{n}}}-\frac{1}{2^{2^{n}}\times2^{2^{n}}}=\frac{1}{2^{2^{n}}}\times(1-\frac{1}{2^{2^{n}}}) . Which isn't too helpful in this form.

But can be written as:

1 2 2 n 1 2 2 n + 1 \frac{1}{2^{2^{n}}}-\frac{1}{2^{2^{n+1}}} Which we can easily use to telescope to infinity leaving 1 2 2 1 = 1 4 \frac{1}{2^{2^{1}}}=\frac{1}{4} .

Alex Burgess - 2 years, 4 months ago

 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
13
from fractions import Fraction

sum_ = 0
for i in range(1,8):
    numer = 2**(2**i)-1
    denom = 2**(2**(i+1))
    sum_ += float(numer)/denom

x= Fraction(sum_).limit_denominator(1000)  
print '\n\nSummation = %s'     % x          
print 'a = %d' % x.numerator    
print 'b = %d' % x.denominator 
print 'a + b = %d'  % (x.numerator+ x.denominator)

1
2
3
4
Summation = 1/4
a = 1
b = 4
a + b = 5

Michael Fitzgerald - 3 years, 2 months ago

But can we do this when we have infinite sum?

Malika Oubilla - 2 years, 9 months ago

Log in to reply

Yes. the series converges.

Chew-Seong Cheong - 2 years, 9 months ago

LaTeX: n = 1 2 2 n 1 2 2 n + 1 \large \sum_{n=1}^{\infty} \frac{2^{2^{n}}-1}{2^{2^{n+1}}} LaTeX: n = 1 2 2 n 1 2 2 n 2 \large \sum_{n=1}^{\infty} \frac{2^{2^{n}}-1}{2^{2^{n}*2}} LaTeX: n = 1 2 1 2 2 \large \sum_{n=1}^{\infty} \frac{2-1}{2^{2}} LaTeX: n = 1 1 4 \large \sum_{n=1}^{\infty} \frac{1}{4} Here, a = 1, b = 4. =>a+b = 5.

Why can we simplify n = 1 2 2 n 1 2 2 n 2 \sum_{n=1}^{\infty} \frac{2^{2^{n}}-1}{2^{2^{n}*2}} to n = 1 2 1 2 2 \sum_{n=1}^{\infty} \frac{2-1}{2^{2}} ?

Samuel Leško - 3 years, 5 months ago

Log in to reply

Every term after the first one have an additive inverse which makes it yield 0. Try telescoping series!

A Former Brilliant Member - 3 years, 5 months ago

The sum of 1/4 from 1 to n is n/4...

Alex Burgess - 2 years, 4 months ago

@ A Brilliant Member - Those last two lines of yours should not have summation notation in front of them. They are just equal to the equivalent of, or exactly, 1/4. Putting the summation from n = 1 to oo in front of them means you would be adding an infinite number of 1/4 terms. That is not what you mean. You need to edit away those last two summation notations.

Dennis Rodman - 2 years, 2 months ago
Ben Major
Jan 30, 2017

You can rewrite the fraction as a sum of 2 fractions: (1/2)^(2^n)-(1/2)^(2^(n+1)). Now why is this more helpful? Well, if you expand it out, you get 1/4-1/16+1/16-1/128+1/128 etc. It sure seems like all the terms after 1/4 cancel out. Well, you can confirm this intuitive solution by considering simple exponent rules. Whenever you subtract a (1/2)^(2^(n+1)) term, you add it back with the next term because the n in the tem (1/2)^(2^n) just increased by 1 as the counter went up by one, making it (1/2)^(2^(n+1)). This term and the one preceding it are opposites, so adding them will cancel out, leaving you with the original term, 1/4=a/b, so a+b=1+4=5. Note: formally, the partial telescoping sum, that is, the sum but only taken up to a finite n can be rewritten as a(1)-a(2)+a(3)-a(4)+...+a(n)-a(n+1). Using the reasoning above we can see that all but a(n+1) will cancel out in the partial sum. Now, we can take lim(n->infty) of a(1)-a(n+1) (the partial sum). Since the exponent of a(n+1) is negative, as n tends to infty the value of this term will tend to 0, leaving you with a(1) as the value of the sum.

What a fun problem!

Stewart Gordon
Dec 10, 2017

n = 1 2 2 n 1 2 2 n + 1 = n = 1 2 2 n 2 2 n + 1 1 2 2 n + 1 = n = 1 ( 2 2 n 2 n + 1 2 2 n + 1 ) = n = 1 ( 2 2 n 2 2 n + 1 ) = 2 2 1 2 2 2 + 2 2 2 2 2 3 + 2 2 3 2 2 4 + = 2 2 1 = 1 4 \large\sum_{n=1}^\infty \frac{2^{2^n}-1}{2^{2^{n+1}}} \\ = \large\sum_{n=1}^\infty \frac{2^{2^n}}{2^{2^{n+1}}} - \frac1{2^{2^{n+1}}} \\ = \large\sum_{n=1}^\infty \left(2^{2^n - 2^{n+1}} - 2^{-2^{n+1}} \right) \\ = \large\sum_{n=1}^\infty \left(2^{-2^n} - 2^{-2^{n+1}} \right) \\ = 2^{-2^1} - 2^{-2^2} + 2^{-2^2} - 2^{-2^3} + 2^{-2^3} - 2^{-2^4} + \ldots \\ = 2^{-2^1} \\ = \boxed{\frac14}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...